2021
DOI: 10.3390/ijerph18041778
|View full text |Cite
|
Sign up to set email alerts
|

Process Evaluation of an Operational-Level Job Stress Intervention Aimed at Decreasing Sickness Absence among Public Sector Employees in Sweden

Abstract: Work-related sickness absence carries large societal costs, and interventions aimed at decreasing sickness absence need to be performed in an effective way. This study evaluated the implementation process of an operational-level job stress intervention, implemented between 2017 and 2018 in the public sector, by assessing the extent to which the allocated resources reached the intended target group, if the planned measures could be expected to address the relevant work environmental challenges, and if the plann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 57 publications
1
12
0
Order By: Relevance
“…This difference in economic benefits between the approaches could be explained by the higher intervention effect in the FSA compared to that in the MSA, where the process evaluation of the two approaches showed that line managers and HR using the MSA needed support with designing interventions that corresponded to the workplace challenges they were facing. Only half of the interventions in the MSA were considered to fit the workplace challenges [ 22 ]; by contrast, there was a high correspondence between implemented interventions and the workplace challenges for the FSA [ 21 ]. The importance of fitting interventions to the context and workplace challenges has been addressed in previous literature [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This difference in economic benefits between the approaches could be explained by the higher intervention effect in the FSA compared to that in the MSA, where the process evaluation of the two approaches showed that line managers and HR using the MSA needed support with designing interventions that corresponded to the workplace challenges they were facing. Only half of the interventions in the MSA were considered to fit the workplace challenges [ 22 ]; by contrast, there was a high correspondence between implemented interventions and the workplace challenges for the FSA [ 21 ]. The importance of fitting interventions to the context and workplace challenges has been addressed in previous literature [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…There was, however, a difference in sickness absence between the participating workplaces with lower total sickness absence in the MSA, suggesting that the potential for impacts was smaller. Interestingly, a previous evaluation showed that the intervention groups with this approach had a significantly higher sickness absence than their respective reference groups, and a higher sickness absence compared to the mean sickness absence in the region [ 22 ], implying a potential to reduce sickness absence for workplaces in both approaches.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations